Whistle from Afar: A Case of Endotracheal Metastasis in Papillary Thyroid Cancer - Bitoti Chattopadhyay; Biswamit Bhattacharya; Atri Chatterjee; Pijush Kanti Biswas; Nirod Baran Debnath (Case Reports in Oncological Medicine)
Endotracheal metastasis is a rare situation, usually associated with malignancies of breast and gastrointestinal tract, specially colon. Papillary carcinoma of thyroid commonly disseminates through lymphatic channels and tracheal involvement through vascular route is rarely reported. Here, we report a case of tracheal metastasis from papillary carcinoma of thyroid. The patient responded to external beam radiation therapy with cobalt 60 beams in a dose of 44 Gy followed by a 16 Gy boost. The patient is under followup and is presently asymptomatic. This paper adds to the repertoire of evidence in treatment of endotracheal metastasis.